Non-linearity between family control and firm financial sustainability: moderating effects of CEO tenure and education - Norazlin, Ahmad; Irene, Wei Kiong Ting; Tebourbi, Imen; Kweh, Qian Long (Springer, 2022)
We investigate the non-linearity between family control and firm financial sustainability and the manner in which CEO tenure and education moderate the non-linear relationship. We apply fixed-effects panel regression and several alternative tests, including two-stage least squares, in studying 2844 firm-year observations of Malaysian publicly listed firms during the period 2009–2019. We find a non-linear U-shaped relationship between family control and firm financial sustainability. Specifically, once levels of family control exceed a certain threshold, the relationship between family control and firm financial sustainability becomes positive. Moreover, CEO tenure and education moderate this non-linearity. That is, when family control is at a low (high) level, both moderators lessen (increase) the negative (positive) effects of family control on firm financial sustainability.